2015
DOI: 10.1021/acs.jafc.5b03836
|View full text |Cite
|
Sign up to set email alerts
|

Cassia tora Seed Extract and Its Active Compound Aurantio-obtusin Inhibit Allergic Responses in IgE-Mediated Mast Cells and Anaphylactic Models

Abstract: Cassia tora seed is widely used due to its various biological properties including anticancer, antidiabetic, and anti-inflammatory effects. However, there has been no report of the effects of C. tora seed extract (CTE) on immunoglobulin E (IgE)-mediated allergic responses. In this research, we demonstrated the effects of CTE and its active compound aurantio-obtusin on IgE-sensitized allergic reactions in mast cells and passive cutaneous anaphylaxis (PCA). CTE and aurantio-obtusin suppressed degranulation, hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 48 publications
0
22
2
Order By: Relevance
“…Among the seven compounds, gluco-obtusifolin has the highest content in seed tissues (Fig 6 and Table 2). It is well known that aurantio-obtusin is the most significant active compound [8] and is distributed mainly in the seed [44]. However, we found that low levels of aurantio-obtusin were observed at the early and late developmental stages.…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…Among the seven compounds, gluco-obtusifolin has the highest content in seed tissues (Fig 6 and Table 2). It is well known that aurantio-obtusin is the most significant active compound [8] and is distributed mainly in the seed [44]. However, we found that low levels of aurantio-obtusin were observed at the early and late developmental stages.…”
Section: Resultscontrasting
confidence: 60%
“…STE and aurantio-obtusin also suppressed IgE-mediated FcεRI such as phosphorylation of Syk, protein kinase Cµ, phospholipase Cγ, and extracellular signal-regulated kinases. This suggests that STE and aurantio-obtusin can be beneficial to the treatment of allergy-related diseases [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the per‐capita consumption worldwide averages 4 fluid ounces per day, and approximately 2.5 million metric tons of dried tea is produced each year, mainly in India, China, Sri Lanka, Turkey, Russia, and Japan . Semen cassiae tea is a popular health tea drink – a roasted tea in Korea and China . It has become a popular health tea drink because it has the function of relaxing the bowels, reducing inflammation in the liver, and improving eyesight and can also be used as a laxative and a tonic.…”
Section: Introductionmentioning
confidence: 99%
“…[2021] C. tora has varied bioactivities, namely, antioxidant,[22] hypolipidemic,[23] larvicidal,[24] antihepatotoxic,[25] antiplasmodial,[26] and anti-inflammatory. [2728] Moreover, a wide range of compounds isolated from this plant such as achrosin, emodin, anthraquinones, apigenin, chryso-obtusin, chrysarobin, chrysophanol, and campesterol showed antioxidant activity. [29] The extract of C. tora showed peroxynitrite scavenging activity which is ascribed to alaternin and norrubrofusarin glucose in it.…”
Section: Introductionmentioning
confidence: 99%
“…[32] Furthermore, C. tora extract and its active component aurantio-obtusin inhibited allergic responses in IgE-mediated mast cells and anaphylactic models. [28] The ethnomedicinal uses of C. tora imply that this plant may be capable of protecting DNA and membrane damage against oxidative stress. The present study is focused to determine the levels of flavonoids in the leaf extracts of C. tora and to determine its role in protecting DNA and membrane damage by oxidative stress.…”
Section: Introductionmentioning
confidence: 99%